Fundamentally altered global- and microstate EEG characteristics in Huntington's disease. Issue 1 (January 2021) - Faber, Pascal L.; Milz, Patricia; Reininghaus, Eva Z.; Mörkl, Sabrina; Holl, Anna K.; Kapfhammer, Hans-Peter; Pascual-Marqui, Roberto D.; Kochi, Kieko; Achermann, Peter; Painold, Annamaria
Highlights: Global states underlying Huntington's disease (HD): reduced connectivity and severity related dimensionality increase. Microstates in HD: classes A & B more prominent, classes C & D less prominent. Cognitive test scores related to global- and microstate properties. Abstract: Objective: Huntington's disease (HD) is characterized by psychiatric, cognitive, and motor disturbances. The study aimed to determine electroencephalography (EEG) global state and microstate changes in HD and their relationship with cognitive and behavioral impairments. Methods: EEGs from 20 unmedicated HD patients and 20 controls were compared using global state properties (connectivity and dimensionality) and microstate properties (EEG microstate analysis). For four microstate classes (A, B, C, D), three parameters were computed: duration, occurrence, coverage. Global- and microstate properties were compared between groups and correlated with cognitive test scores for patients. Results: Global state analysis showed reduced connectivity in HD and an increasing dimensionality with increasing HD severity. Microstate analysis revealed parameter increases for classes A and B (coverage), decreases for C (occurrence) and D (coverage and occurrence). Disease severity and poorer test performances correlated with parameter increases for class A (coverage and occurrence), decreases for C (coverage and duration) and a dimensionality increase. Conclusions: Global state changes may reflect higher functional dissociation between brain areas and the complex microstate changes possibly the widespread neuronal death and corresponding functional deficits in brain regions associated with HD symptomatology. Significance: Combining global- and microstate analyses can be useful for a better understanding of progressive brain deterioration in HD.